(untitled) (Research, Society and Development, 2024)
Gestational Diabetes Mellitus - GDM, is due to the occurrence of Hyperglycemia, the acumulativo of glucose in the blood of women who are pregnant. This occurrence is due to a defect in the secretion or action of insulin, a hormone that is produced in the pancreatic organ through beta cells. Objective: To understand the strategies used by primary care nurses in the prevention of gestational diabetes. Methodology: Narrative Review, through a descriptive approach and qualitative analysis. Results: identifying the selection of articles from magazines, books, annals and portal, used to compose the textual body. Thus, 3 books of scientific methodology, a consultation in a portal, a collection of an anal and 15 journal articles in the period 2019-2023 were used. Final Considerations: In Primary Care, the nursing professional, has to be qualified and trained to provide nursing care for pregnant women and the fetus, even as the management developed by Primary Care, lacks a greater bond between the professional, the family and the pregnant woman.